Intra-abdominal small intestinal desmoid tumour mimicking GIST - Eswaravaka, Sai Krishna (BMJ Case Rep, 2021)
Desmoid tumours, also known as aggressive fibromatosis, are fibromuscular neoplasms that arise from mesenchymal cell lines. Desmoid tumours are usually benign and are locally aggressive tumours. We report a case of a 31-year-old man presenting with abdominal mass associated with dyspepsia and early satiety. CT scan demonstrated a large heterogeneous mass adherent to or arising from the jejunum. The patient underwent a successful elective exploratory laparotomy with resection of the tumour arising from the wall of the ileum with a 10 cm margin. The patient had an uneventful recovery and no recurrence at 6-month follow-up. Pathology report and immunohistochemistry analysis revealed the mass to be a primary desmoid tumour of the small bowel, as the tumour was negative for c-kit and Discovered on GIST 1 (DOG-1) and positive for beta-catenin and smooth muscle actin.